Metode Kritik Matn Hadis Menurut al-Daraqutni - Mohd Aizul Yaakob (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2023)
Hadith criticism is one of the important disciplines in evaluating the authenticity of a hadith. The field of hadith criticism can be divided into two, namely sanad criticism and matan criticism. There are some orientalists who explain that hadith scholars only focus on the criticism of the sanad of transmission and ignore the criticism of the matan of the hadith. Thus there is a gap in their assessment. This claim is a mistake, it has even been proven by al-Daraqutni's own practice through the book al-'Ilal al-Waridah fi al-Ahadith al-Nabawiyyah. This study uses a qualitative method and the data is completely collected based on the document analysis method. The findings of the study show that there are at least six criticism methodologies that have been practiced by al-Daraqutni in the book al-'Ilal al-Waridah fi al-Ahadith al-Nabawiyyah. This finding also indirectly refutes the claims of some orientalists who state that there is a gap in the discourse of Matan criticism by hadith scholars. This finding also highlights al-Daraqutni's prominence in the field of hadith and the position of his book, al-'Ilal al-Waridah fi al-ahadith al-Nabawiyyah.